2013
DOI: 10.4103/2225-4110.107700
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention by Traditional Chinese Herbal Medicine and Dietary Phytochemicals: Targeting Nrf2-Mediated Oxidative Stress/Anti-Inflammatory Responses, Epigenetics, and Cancer Stem Cells

Abstract: Excessive oxidative stress induced by reactive oxygen species (ROS), reactive nitrogen species (RNS), and reactive metabolites of carcinogens alters cellular homeostasis, leading to genetic/epigenetic changes, genomic instability, neoplastic transformation, and cancer initiation/progression. As a protective mechanism against oxidative stress, antioxidant/detoxifying enzymes reduce these reactive species and protect normal cells from endo-/exogenous oxidative damage. The transcription factor nuclear factor-eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 159 publications
(166 reference statements)
0
29
0
Order By: Relevance
“…Consequently, the oxidative stress produced by high levels of ROS/RNS during normal cell metabolism leads to potential damage, causing oxidative damage to large biomolecules, such as lipids, proteins, and DNA, which may eventually lead to mutations and ultimately, cancer development [25]. Similarly, oxidative stress also has a significant association with many other chronic diseases, such as neurodegenerative diseases (e.g., Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis), cardiovascular disease, diabetes, and inflammatory diseases [26-28]. In this context, the major chemoprevention mechanisms mediated by dietary glucosinolate derivatives include modulation of phase I drug metabolic enzymes (e.g., cytochrome P450 family, CYP), which prevent procarcinogenic molecule formation and the induction of phase II/detoxifying enzymes (e.g., GST; UDPglucuronosyl transferases, and UGT), which catalyze conjugation reactions to inactivate or detoxify exogenous (e.g., carcinogens and other xenobiotics) and endogenous compounds (e.g., sex steroid hormones) related to cancer development [29-31].…”
Section: Dietary Glucosinolate Derivatives and Modulation Of Phase I mentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the oxidative stress produced by high levels of ROS/RNS during normal cell metabolism leads to potential damage, causing oxidative damage to large biomolecules, such as lipids, proteins, and DNA, which may eventually lead to mutations and ultimately, cancer development [25]. Similarly, oxidative stress also has a significant association with many other chronic diseases, such as neurodegenerative diseases (e.g., Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis), cardiovascular disease, diabetes, and inflammatory diseases [26-28]. In this context, the major chemoprevention mechanisms mediated by dietary glucosinolate derivatives include modulation of phase I drug metabolic enzymes (e.g., cytochrome P450 family, CYP), which prevent procarcinogenic molecule formation and the induction of phase II/detoxifying enzymes (e.g., GST; UDPglucuronosyl transferases, and UGT), which catalyze conjugation reactions to inactivate or detoxify exogenous (e.g., carcinogens and other xenobiotics) and endogenous compounds (e.g., sex steroid hormones) related to cancer development [29-31].…”
Section: Dietary Glucosinolate Derivatives and Modulation Of Phase I mentioning
confidence: 99%
“…Recently, a large amount of evidence has demonstrated that epigenetic alterations, such as DNA methylation, histone modifications and non-coding miRNAs, consistently contribute to carcinogenesis, and constituents in the diet, including dietary glucosinolate derivatives, have the potential to alter a number of these epigenetic events [18, 15, 26]. Although most research on the cellular effects of dietary glucosinolate derivatives has primarily focused on detoxifying enzyme effects, increasing evidence has demonstrated the chemopreventive effects of dietary glucosinolate derivatives on the regulation of silenced genes in cancer.…”
Section: Dietary Glucosinolate Derivatives and Epigenetic Mechanisms mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that cellular mechanisms contribute to the overall cancer-prevention effects of these dietary phytochemicals [33]. Natural phytochemicals from certain plants have the capability to affect the epigenome and can also trigger sustained DNA damage and apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%